A Proposal for a Unifying Set of Definitions of Fatigue - Skau, Simon; Sundberg, Kristoffer; Kuhn, Hans-Georg (Frontiers in Psychology, 2021)
In this paper, we propose a set of unifying definitions that are useful in all areas of fatigue research while remaining neutral to the various theories about fatigue. We first set up two criteria and four desid-erata that a definition for interdisciplinary use needs to fulfill: i) non-circularity, ii) finiteness, iii) broad-ness, iv) precision, v) neutrality, and vi) phenomena-focused. We argue that other existing attempts to unify definitions within fatigue research do not fulfill all of these criteria and desiderata . Instead, we argue for a set of stipulative definitions, centered around performance measures and subjective estima-tions, is required in order to maximize clarity. In total, a set of 17 distinct definitions of fatigue and fa-tigue-related phenomena is presented. These definitions will help facilitate communication between dif-ferent researchers, link phenomena from divergent research fields together, facilitate application and knowledge production, and increase the specificity for hypothesis testing.